Evaluation of Risk Factors for Type 2 Diabetes in Population Living in City of Yazd: A Case-Control Study - Hassan Saadati; Mohammad Hassan Lotfi; Mohammad Afkhami Ardakani (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Diabetes Mellitus (DM) is one of the most common chronic diseases in the world and the most challenging health problems of the twenty first century. This disease is common in Yazd and has a high prevalence in the province. Due to not available analytic study, the aim of this study was to determine the risk factors of type 2 diabetes among the adult Yazd population, Iran. Materials and Methods: This hospital base case-control study was conducted on the urban population of Yazd city, Iran from 2012 to 2013.A total of 400 subjects including 200 diabetes cases and 200 controls matched by sex and age (±2 years)were studied. Subjects were interviewed face-to-face by trained interviewers using pretested questionnaires. Data were analyzed by descriptive statistics and appropriate statistical tests such as chi- square, student t- test and multiple logistic regressions. Results: The logistic regression model showed that family history of diabetes in first-degree relatives (OR=9.37, P<0.0001), history of dyslipidemia (OR=4.89, P<0.0001), family history of dyslipidemia (OR=2.53, P=0.009), type oil consumption (OR=2.16, P=0.021), type vegetable consumption (OR=4.81, P4 kg (OR=63.89, P=0.001),were considered as associated risk factors for diabetes. Conclusion: The present study showed that family history of diabetes in first-degree relatives, family history of dyslipidemia, history of dyslipidemia, Waist-hip ratio, consumption of fruit, Consumption of vegetables, Type of oil consumption, History of child birth >4 kg and low HDL were positively associated with diabetes.